ENZYMATIC AND PHYTOCHEMICAL ANALYSIS OF ENDOPHYTIC FUNGI ON AEGLE MARMELOS FROM WESTERN GHATS OF TAMIL NADU, INDIA.: Life Sciences-Pharmaceuticals - MANON MANI, VELLINGIRI; GNANA SOUNDARI, AROCKIAM JEYASUNDAR PARIMALA; PREETHI, KATHIRVEL (International Journal of Life Science and Pharma Research, 2018)
Fungal species expands an endophytic role inside the tissues of medicinal plants and are known to produce metabolites, phytochemicals and enzymes in a wide range with biological properties. In the present investigation, the most dominant and potent endophytic fungal strains of Aeglemarmelos, an ethno medicinal plant prevalent in the forest of Western Ghats, Tamil Nadu, India were screened for ability to produce exoenzymes like amylase, protease, lipase, cellulase, laccase and xylanase. The representative potent strains were Curvulariaaustraliensis(FC2AP)and Alternariacitrimacularis(FC8ABr) belonged to the same order Pleosporales. The growth of the endophytic fungi was similar with the highest mycelia formation in the respective media. These endophytic fungal strains produced extracellular enzymes in different pH at different incubation period in a considerable range. Furthermore, the endophytes produced phytochemicals constituents flavonoids and phenols, and this unveils that the strains have highest antioxidant properties. The production of enzymes and phytochemicals provided the insights into their origin and ecological role in the host plant. Hence, this study explains the production and biological activity of enzymes and phytochemicals in endophytic fungi.